(untitled) (Research, Society and Development, 2022)
To assess adherence to pre-exposure prophylaxis (PrEP) to HIV after 3 years of implementation in the Unified Health System (SUS). Ecological, quantitative study, carried out in 2021, in Brazil. Data on HIV PrEP were collected in the monitoring panel provided by the Ministry of Health – Federal Government. The variables studied were type of population, age group, education, race/color; number of dispensations in Brazil from January 2018 to February 2021, number of health services offering PrEP, discontinuation of PrEP, number of new users per month, number of active users per month and sexual habits. Data were tabulated in excel and descriptive statistical analysis was performed for all variables, the chi-square test to verify the association between the variables "discontinuity of PrEP" and "type of key population" and the binomial test of two proportions to compare sexual habits in the first and last consultations. Most of the population is gay or men who have sex with men (82.6%), age group between 30 and 39 years old (51%), white or yellow color (57.2%), 12 years or more of schooling (71%). 42% of subjects discontinued treatment at some point. There was a statistically significant association between the variables “discontinuity of PrEP” and “type of key population”, and a decrease in condom use and in the number of sexual partners between the first and last consultations. Although adherence to the method is increasing, discontinuity in treatment among users is high, which makes success in effectiveness difficult.